VULNERABILITY OF DEVIANT BEHAVIOR AND THE LIVES OF STREET CHILDREN IN THE MUSHROOM HOUSE - Rita Laksmitasari Rahayu; Ryan Hidayat; Fauzi Rahman (Universitas PGRI Sumatera Barat, 2021)
Some children in Sukanagalih Village have the vulnerability to become street children. This is due to the inability of the family to fulfill their needs, which encourages them to work in the mushroom barns. In general, they still live with their families, but most of their life outside the home, they work in mushroom barns after working they become parking brokers. Street children are the generation that belongs to the country who must be nurtured, guided, and directed in kindness. Life motivation and enthusiasm are the keywords for them to achieve the success they dream of. Motivation is a process where activities are initiated, directed, and sustained so that certain needs are met. This need can be either psychological or physical. It is important to point out that motivation looks different to everyone, depending on their needs and values. The community service team provides socialization and understanding of life motivation for children who work part time in mushroom barns who are prone to becoming street children. The location of community service is Cianjur, West Java. Implementation time is November 14, 2020 - January 31, 2021. Methods of community service by giving lectures, conducting questions and answers, and discussion. The mindset of the children of part-time workers in this mushroom barn is still not advanced. It is necessary to change the mindset of these children so that they are not only satisfied with the artificial conveniences offered on the streets. As a result of this service to society, the children of part-time workers feel happy and feel appreciated and are expected to form habits and leave memories.